Referências religiosas na obra de Bert Hellinger: as influências do cristianismo, do taoismo e da cultura zulu na constelação familiar - Martins, Bernardo Penteado de Sousa (2022)
This investigation examined the religious influences in Bert Hellinger's work, a German priest (1925-2019) and founder of Family Constellation, a philosophy of life and therapeutic system. Hellinger worked as a missionary for 16 years in South Africa and, in the last fifty years of his life, he dedicated himself to learning different forms of therapies and creating his own therapeutic approach (Familienstellen). However, our focus in this study was not therapeutic; the scope was to understand his work through the lens of Religious Studies. In this way, we examined the religious influences behind the orders (or laws) that comprise Hellinger's philosophy including Christian references (from his training as a priest), Zulu culture (from his experience as a missionary in South Africa), Taoist influences (from his readings of Lao-Tzu) and psychological influences (from his studies of psychological theories and practices and their relationship with holistic therapies). All these traditions and practices helped Hellinger to outline a therapeutic path and a worldview that points, in its fundamental aspects, to a New Age ethos. To fulfil this goal, this work combined literature review and autoethnographic research. Parallels were found in Family Constellation and in the work of Bert Hellinger, not only with the aforementioned religious references but also with other practices and traditions such as Cosmic Power meditation, a method created by his wife Sophie Hellinger, and shamanism, due to the friendship and possible influence of the shaman Tata Cachora on Hellinger's later ideas. The absence of studies on the subject and the need for further investigations, as well as the possible relevance of the Family Constellation phenomenon to the study of religiosity in the contemporary world, were factors that inspired us to develop this study